2021
DOI: 10.1111/ijcp.14182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID‐19 medications on corrected QT interval and induction of torsade de pointes: Results of a multicenter national survey

Abstract: All authors take responsibility for all aspects of the reliability and freedom from bias of the data presented and their discussed interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
0
25
2
Order By: Relevance
“…The association between remdesivir and the QTc interval prolongation has been observed in a few reports. 14 , 16 - 17 In a recent study, 9% of patients (6/67) who received remdesivir had QTc interval prolongation. Their analysis showed that receiving remdesivir alone was not a predictor of the QTc interval prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…The association between remdesivir and the QTc interval prolongation has been observed in a few reports. 14 , 16 - 17 In a recent study, 9% of patients (6/67) who received remdesivir had QTc interval prolongation. Their analysis showed that receiving remdesivir alone was not a predictor of the QTc interval prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Oseltamivir is an antiviral drug that inhibits Neuraminidase, expressed on the viral surface, which plays an essential role in viral entry to host cells, viral release from infected cells, and subsequent viral spread. Although its role in COVID-19 is very limited, it is noteworthy to mention that Haghjoo et al 51 reported that this drug may significantly prolong QTc when used in combination with HCQ, as also suggested by Çelik et al 56 . No TdP were noted in these patients, as in previous pre-clinical models which tested oseltamivir therapy alone, since this drug is capable to inhibits both inward and outward currents 57 .…”
Section: Mechanisms Of Qt Prolongationmentioning
confidence: 81%
“…It should be noted that in this case, patients were also on AM while receiving remdesivir, which is well-known to prolong the QT interval. Remdesivir monotherapy has indeed shown to prolong QTc in the Haghjoo et al 51 analysis, although keeping a low-risk profile in terms of QT prolongation and TdP induction. Moreover, no major cardiac arrhythmia events were described in the largest trial assessing remdesivir efficacy and safety profile.…”
Section: Mechanisms Of Qt Prolongationmentioning
confidence: 92%
See 2 more Smart Citations